2015
DOI: 10.1038/npp.2015.310
|View full text |Cite|
|
Sign up to set email alerts
|

State-Dependent Partial Occlusion of Cortical LTP-Like Plasticity in Major Depression

Abstract: The synaptic plasticity hypothesis of major depressive disorder (MDD) posits that alterations in synaptic plasticity represent a final common pathway underlying the clinical symptoms of the disorder. This study tested the hypotheses that patients with MDD show an attenuation of cortical synaptic long-term potentiation (LTP)-like plasticity in comparison with healthy controls, and that this attenuation recovers after remission. Cortical synaptic LTP-like plasticity was measured using a transcranial magnetic sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 52 publications
3
40
1
2
Order By: Relevance
“…More recently, an investigation using a PAS protocol in patients with MDD further supported this hypothesis by showing that cortical LTP-like plasticity was significantly decreased in a state-dependent manner in a group of 27 patients who suffered an acute episode of MDD. Interestingly, this study clearly showed that LTP-like plasticity was restored after remission (Kuhn et al., 2016). Finally, after facilitatory PAS, changes in cortical excitability were linked to associative LTP.…”
Section: Tms In Depressionmentioning
confidence: 70%
See 1 more Smart Citation
“…More recently, an investigation using a PAS protocol in patients with MDD further supported this hypothesis by showing that cortical LTP-like plasticity was significantly decreased in a state-dependent manner in a group of 27 patients who suffered an acute episode of MDD. Interestingly, this study clearly showed that LTP-like plasticity was restored after remission (Kuhn et al., 2016). Finally, after facilitatory PAS, changes in cortical excitability were linked to associative LTP.…”
Section: Tms In Depressionmentioning
confidence: 70%
“…The articles reviewed here provide neurophysiological evidence for altered cortical excitability (Maeda et al., 2000; Fitzgerald et al., 2004; Levinson et al., 2010; Spampinato et al., 2013; Concerto et al., 2013; Croarkin et al., 2013; Veronezi et al., 2016) and synaptic plasticity (Chroni et al., 2008; Bajwa et al., 2008; Spampinato et al., 2013; Croarkin et al., 2013; Player et al., 2013; Kuhn et al., 2016) in MDD. These data confirm the findings of previous investigations that have used different approaches (Debener et al., 2000; Normann et al., 2007; Teyler and Cavus, 2007; Salustri et al., 2007; Nissen et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, studies of cortical excitability and by extension neuronal plasticity in MDD, have reported consistent evidence for changes in LTP-like plasticity in patients with depression. Using a paired associative stimulation protocol, with transcranial stimulations, one study has identified impaired LTP-like plasticity in MDD patients who possess reduced motor evoked potential amplitudes, when compared with healthy controls (Kuhn et al, 2016). This finding was particularly interesting, as these reductions in motor evoked potential amplitudes were restored after MDD patients had entered remission (Kuhn et al, 2016).…”
Section: Altered Synaptic Plasticity In Mddmentioning
confidence: 99%
“…Scientifically, sleep deprivation presents a unique paradigm to study rapid mechanisms of antidepressant response and relapse, which are most likely different from those of today's standard treatments. We recently proposed a new framework of mechanisms [44] which integrates two prominent lines of research on MDD and sleep, the synaptic plasticity hypothesis of MDD [45,46] and the synaptic homeostasis hypothesis of sleep-wake regulation [47]. The figure depicts the proposed interplay between the time course of net synaptic strength (homeostatic plasticity; solid and dotted lines) and the inducibility of synaptic LTP (associative plasticity; red window).…”
Section: Box 1 Therapeutic Sleep Deprivation In Major Depressionmentioning
confidence: 99%